Zebrafish embryos as an alternative to animal experiments: a commentary on the definition of the onset of protected life stages in animal welfare regulations - Strähle, Uwe; Braunbeck, Thomas (Reproductive toxicology, 2012)
Worldwide, the zebrafish has become a popular model for biomedical research and (eco)toxicology. Particularly the use of embryos is receiving increasing attention, since they are considered as replacement method for animal experiments. Zebrafish embryos allow the analysis of multiple endpoints ranging from acute and developmental toxicity determination to complex functional genetic and physiological analysis. Particularly the more complex endpoints require the use of post-hatched eleutheroembryo stages. According to the new EU Directive 2010/63/EU on the protection of animals used for scientific purposes, the earliest life-stages of animals are not defined as protected and, therefore, do not fall into the regulatory frameworks dealing with animal experimentation. Independent feeding is considered as the stage from which free-living larvae are subject to regulations for animal experimentation. However, despite this seemingly clear definition, large variations exist in the interpretation of this criterion by national and regional authorities. Since some assays require the use of post-hatched stages up to 120h post fertilization, the literature and available data are reviewed in order to evaluate if this stage could still be considered as non-protected according to the regulatory criterion of independent feeding. Based on our analysis and by including criteria such as yolk consumption, feeding and swimming behavior, we conclude that zebrafish larvae can indeed be regarded as independently feeding from 120h after fertilization. Experiments with zebrafish should thus be subject to regulations for animal experiments from 120h after fertilization onwards.
Available online 25 June 2011
Gesehen am 26.08.2020